Full stack GraphQL applications : with REACT, NODE.JS, and NEO4J - Lyon, William (Manning Publications, 2022)
The GraphQL query language radically reduces over-fetching or under-fetching of data by constructing precise graph-based data requests. In Full Stack GraphQL Applications you’ll learn how to build graph-aware web applications that take full advantage of GraphQL’s amazing efficiency. Neo4j’s William Lyon teaches you everything you need to know to design, deploy, and maintain a GraphQL API from scratch. He reveals how you can build your web apps with GraphQL, React, Apollo, and Neo4j Database, aka “the GRANDstack,” to get maximum performance out of GraphQL. Full Stack GraphQL Applications teaches you to build graph-aware web applications using GraphQL, React, Apollo, and the Neo4j database, collectively called “the GRANDstack.” Practical, hands-on examples quickly develop your understanding of how the GRANDstack fits together. As you go, you’ll create and deploy to the cloud a full-featured web application that includes search, authentication, and more. Soon, you’ll be ready to deploy end-to-end applications that take full advantage of GraphQL’s outstanding performance.